From Classrooms to Innovation Ecosystems: AI-Enhanced STEAM Education in Primary Schools of Atlántico, Colombia - Vizcaino Lascano, Daisy Margarita; Vizcaino Lascano, Daisy Margarita (Corporación universitaria Americana, 2026)
Introduction: Artificial intelligence (AI) is increasingly emerging as a strategic lever for modernizing education; however, its integration into primary education in emerging regions remains uneven and, often, out of context. Objective: This article proposes and evaluates an AI-enhanced STEAM (science, technology, engineering, arts, and mathematics) framework designed for elementary schools in Atlántico, Colombia. Methodology: The study integrates adaptive learning, collaboration between teachers and AI, and project-based STEAM labs that address local challenges. A mixed-methods design is used: (i) a qualitativephenomenological component that captures the experiences of teachers and students, and (ii) a quasi-experimental component that compares an AI-STEAM group and a control group in terms of indicators of participation, problem-solving, creativity, andcollaborative behaviors. Results: The findings show consistent improvements in performance growth, participation rates, and innovative behaviors in the classroom within the intervention group, supported by a one-way ANOVA and complementary visual analyses (progress curves, bar charts, and box plots). Conclusions: The findings suggest that AI-powered STEAM can help schools move beyond the mere transmission of content toward ecosystems of early-stage innovation that promote equity, autonomy, and regional capacity building.